1994
DOI: 10.1007/bf01408596
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of steel 20KhN2M after laser treatment

Abstract: Steel 20KhN2M is used for the production of gears and other components, for whose service enhanced wear resistance is required in retaining resistance to bnpact loadings. The deforvnation (warping) and increased brittleness of these components are observed after their bulk hardening. The deformation of the components cannot be completely eliminated, even on hardening with the use of superhigh-frequency radiation. Local laser heating lowers defopvnation to a significant degree, hz this connection, it was intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The x-ray chemical analysis has shown that the alloy contains 2.78 at.% of Si, 0.3 at.% of Cr, 1.2 at.% of Mn and about 14.5 at.% of C. The microscopic studies revealed that carbon existed as the graphite insertions in the layered structure with the distance of some micrometres between the graphite layers. The structure of grey cast iron is favourable for the research because, differing from laser implantation [8], carbon does not evaporate from the surface and mixes with iron successfully. A small amount of other impurities in grey cast iron allows the successful study of the formation of the phases of martensite, iron carbides and retained austenite on the basis of this system.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…The x-ray chemical analysis has shown that the alloy contains 2.78 at.% of Si, 0.3 at.% of Cr, 1.2 at.% of Mn and about 14.5 at.% of C. The microscopic studies revealed that carbon existed as the graphite insertions in the layered structure with the distance of some micrometres between the graphite layers. The structure of grey cast iron is favourable for the research because, differing from laser implantation [8], carbon does not evaporate from the surface and mixes with iron successfully. A small amount of other impurities in grey cast iron allows the successful study of the formation of the phases of martensite, iron carbides and retained austenite on the basis of this system.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…The production of magnetic nanocrystalline particles is widely investigated at present [5,6]. It has been demonstrated that material synthesis and its modification using laser radiation offer some advantages [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…After the laser treatment the surface hardness of the metal increases by a factor of 3-3.5 and the wear resistance increases twofold compared to the initial value, which is associated with grain disintegration [23].…”
mentioning
confidence: 99%